New concept: cellular senescence in pathophysiology of cholangiocarcinoma. (3rd May 2016) - Sasaki, Motoko; Nakanuma, Yasuni
ABSTRACT: Cholangiocarcinoma, a malignant tumor arising in the hepatobiliary system, presents with poor prognosis because of difficulty in its early detection/diagnosis. Recent progress revealed that cellular senescence may be involved in the pathophysiology of cholangiocarcinoma. Cellular senescence is defined as permanent growth arrest caused by several cellular injuries, such as oncogenic mutations and oxidative stress. "Oncogene-induced" and/or stress-induced senescence may occur in the process of multi-step cholangiocarcinogenesis, and overexpression of a polycomb group protein EZH2 may play a role in the escape from, and/or bypassing of, senescence. Furthermore, senescent cells may play important roles in tumor development and progression via the production of senescence-associated secretory phenotypes. Cellular senescence may be a new target for the prevention, early diagnosis, and therapy of cholangiocarcinoma in the near future.